The influence of surface topography of UV coated and printed cardboard on the print gloss - Igor Karlović; Dragoljub Novaković; Erzsébet Novotny (Journal of Graphic Engineering and Design, 2010)
The incident light on the printed surface undergoes through several processes of scattering, absorbtion and reflectiondepending on the surface topography and structure of the material. The specular part of the surface reflection is commonlyattributed as the geometric component of the reflection, and when measured is associated with specular gloss.The diffuse part of the surface reflection contains the chromatic part of the reflection and is commonly calculatedthrough colorimetric values. Using UV coatings as surface enhacement materials which affect the optical propertiesof coated surfaces and final appearance of the printed product forms new surface topography over the existingone. We have investigated the influence of three different amounts of UV glossy and matte oveprint coating on themeasured specular gloss of printed cardboard samples. The different amount of coatings on the printed samples wereachived using three different screen stencils of 180 threads/cm, 150 threads/cm and 120 threads/cm thread count.The cardboard samples were analysed with AFM and SEM microscopes to obtain surface topography and roughnessvalues which were evaluated with the measured geometric values speficied as instrumental gloss. The surfaceswith a specific amount of UV coatings showed a new formed topography which influences the reflection of light.The changes in topography were evaluated through surface roughness parameters which showed a decline of surfaceroughness with tht additional ammount of glossy and matte coatings. The obtained and calculated correlations showthere is a high correlation between coating ammount and surface roughness change and gloss for the glossy UVcoating. The results for the matte UV coatings showed lower correlation for the gloss and surface roughness.